Human Resource Management Strategies for Engagement and Talent Attraction in Hybrid Work Models - Ramachandaran , Sharmila Devi; Thet, Khine Zar Zar; Qalati, Sikandar Ali; Doraisingam, Puspanathan; Malek, Bahiah A; Kumari, Sonia (Journal of Ecohumanism, 2024)
The aim of this paper is to explore HR strategies for enhancing employee engagement and attracting talent within hybrid environments. By reviewing existing literature, the study evaluates the effective communication tools, career development opportunities, and the role of transparent feedback mechanisms in hybrid work settings. The finding of the study emphasizes the necessity of flexible work arrangements, strategic use of digital tools, and fostering a supportive virtual culture to preserve high levels of engagement. Although advancement follows, studies show considerable gaps regarding the specific HR mechanism and their effectiveness in hybrid contexts. Future studies should address these gaps by considering the impact of these strategies across diverse cultural contexts and organizational settings.